2012
DOI: 10.1155/2012/372395
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Urban Stream Sediments

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are persistent organic pollutants of high environmental concern with known carcinogenic activity. Although literature documents PAH fate in urban runoff, little is known about their distribution on sediment sizes, which is essential for determining their treatability and fate in receiving waters. This paper has quantified the concentrations of selected PAHs in urban creek sediments and examined possible relationships between sediment PAH content and sediment characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Suspended sediment is particularly inconvenient for the environment. Fine particles affect the colour and turbidity of water, and are also carriers of other pollutants, including: heavy metals (Herngren et al 2005), radionuclides (Walling 2006), phosphorus compounds (Hejduk 2011), polycyclic aromatic hydrocarbons (Bathi et al 2012), and pharmaceuticals (Sikorska et al 2012). Consequently, they can pose a threat to human health, or to the proper functioning of ecosystems, even far away from the place of their creation.…”
Section: Introductionmentioning
confidence: 99%
“…Suspended sediment is particularly inconvenient for the environment. Fine particles affect the colour and turbidity of water, and are also carriers of other pollutants, including: heavy metals (Herngren et al 2005), radionuclides (Walling 2006), phosphorus compounds (Hejduk 2011), polycyclic aromatic hydrocarbons (Bathi et al 2012), and pharmaceuticals (Sikorska et al 2012). Consequently, they can pose a threat to human health, or to the proper functioning of ecosystems, even far away from the place of their creation.…”
Section: Introductionmentioning
confidence: 99%
“…The high molecular weight PAHs had a greater portion associated with the particulates than did the low molecular weight PAHs. Bathi (2008) found that overall, all characteristics studied showed similar trends, with the smaller and larger particles found to have relatively higher values compared to the intermediate sized particles. Cluster analyses of the PAH concentrations for the different particle sizes showed that for most cases examined, the LOM (light organic matter) fraction was found to be a statistically separate sample category (having much higher concentrations) from all other sizes.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 57%
“…In this specific case, the higher particulate strengths associated with larger particle size ranges may be related to the nature of the runoff particulates from the site due to large organic material from the adjacent landscaped areas. Bathi (2008) investigated Tuscaloosa, Alabama urban area stream sediment polycyclic aromatic hydrocarbon (PAH) values for different size ranges. PAHs can occur in soluble and particulate associated forms; however, previous studies have shown that particulate associated PAHs are most abundant in stormwater (Pitt et al 1999;Mahler et al 2005;Hwang and Foster 2006).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…A study by Waschbush et al (1999) found that particles larger than 250µm in size contributed nearly 50% of the mass of total phosphorus and leaf material contributed an additional 30%. Bathi et al (2012) found that PAH concentrations had a bimodal distribution with concentrations being the highest when associated with particles less than 90µm and greater than 710µm in size. 13 PAHs were sampled at 3 locations, and all but 4 of the PAH-location combinations showed significant differences in PAH concentration by particle size.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%